Tinjauan Yuridis Terhadap Upaya Penegakkanhukum dalam Mengatasi Penyebaran Uang Palsu - Kusuma, Ibnu (Proceedings Series on Social Sciences & Humanities, 2024)
In this case, the author looks at several social facts that occur where the application of the law is not in accordance with the crime committed because imprisonment for a maximum of 1 year with a fine of 200,0000.ooo.00 (two hundred million rupiah) is not commensurate with the loss to the state's economy, therefore There must be adjustments to sanctions so that criminals who distribute counterfeit money can be deterred so as not to cause problems that are detrimental to both the state and society. The method applied in this article uses normative juridical law by collecting data such as laws, according to experts and journals that are in line with With the title of this scientific article, the conclusion of this scientific work is that the circulation of counterfeit money is very detrimental from various aspects, in terms of the country's economy, society and banking. The author's suggestion is to implement sanctions that provide a deterrent effect for perpetrators of the crime of circulating counterfeit money.